2020
DOI: 10.1029/2019ef001274
|View full text |Cite
|
Sign up to set email alerts
|

In Water‐Limited Landscapes, an Anthropocene Exchange: Trading Lakes for Irrigated Agriculture

Abstract: Lakes-quintessential features of Earth's surface prized from perspectives of water security, aquatic ecosystems, and recreation alike-are shrinking in water-limited regions of all of Earth's inhabited continents. Here we assessed Landsat-derived long-term decrease in global lake area relative to historical lake extent aiming to determine the role of recent Anthropocene levels of irrigated agriculture in the global phenomenon of lake desiccation. As of 2015, 11% (1.8 · 10 5 km 2 ) of global lake area has alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…In many arid parts of the region, especially in Central Asia, changes in lake surface area are caused by factors related to land use change. Chief among these factors is the extraction or diversion of water for agriculture, which would otherwise flow into terminal lakes (Bai et al 2011, Wine andLaronne 2020). Reservoir and dam construction is another type of human interference that has affected both the runoff regime and volume of flow into lakes and outlets (Nilsson and Berggren 2000, Pueppke et al 2018, Schmutz and Moog 2018.…”
Section: Habitat Area and Habitat Degradationmentioning
confidence: 99%
“…In many arid parts of the region, especially in Central Asia, changes in lake surface area are caused by factors related to land use change. Chief among these factors is the extraction or diversion of water for agriculture, which would otherwise flow into terminal lakes (Bai et al 2011, Wine andLaronne 2020). Reservoir and dam construction is another type of human interference that has affected both the runoff regime and volume of flow into lakes and outlets (Nilsson and Berggren 2000, Pueppke et al 2018, Schmutz and Moog 2018.…”
Section: Habitat Area and Habitat Degradationmentioning
confidence: 99%
“…Globally, the surface area of many endorheic lakes is shrinking, a process in which irrigated agriculture plays a key role (Wang et al 2018, Wine andLaronne 2020). The Aral Sea is a paradigmatic example of the destiny of a terminal lake that shrank due to a grossly reduced water inflow caused by excessive water extraction for agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…In the High Plains in the USA, the water level of aquifers has declined substantially due to the large irrigation water withdrawal (McGuire, 2014). A study focusing on global lakes revealed that ∼11% of the lake area has been lost until 2015 mainly due to irrigation water withdrawal (Wine & Laronne, 2020).…”
Section: 1029/2022ms003074mentioning
confidence: 99%